2009
DOI: 10.4103/0973-1482.59913
|View full text |Cite
|
Sign up to set email alerts
|

Spinal epidermoid cyst with sudden onset of paraplegia

Abstract: Spinal epidermoid cysts, whether congenital or iatrogenic, are relatively uncommon in the spinal cord. When they occur, the typical location is in the subdural, extramedullary space of the lumbo-sacral region. We describe an unusual presentation in a 3-year-old male child which mimicked astrocytoma clinicoradiologically. The child developed sudden onset of inability in walking and weakness of both lower limbs after a fall. There was a dramatic reversal of symptoms after surgery. Histopathology revealed an epid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 5 publications
0
23
0
Order By: Relevance
“…25 While the gradual onset of weakness has been described, Munshi et al reported sudden paraplegia in one patient due to inflammation following rupture of the epidermoid cyst, which produced serious symptoms and reduced quality of life. 26 Radical removal of the cyst and preservation of neurological function should be the goal of surgical intervention for spinal epidermoid and dermoid cysts. Because epidermoid and dermoid cysts grow through cisterns, the neural structures may be differentially involved.…”
Section: Discussionmentioning
confidence: 99%
“…25 While the gradual onset of weakness has been described, Munshi et al reported sudden paraplegia in one patient due to inflammation following rupture of the epidermoid cyst, which produced serious symptoms and reduced quality of life. 26 Radical removal of the cyst and preservation of neurological function should be the goal of surgical intervention for spinal epidermoid and dermoid cysts. Because epidermoid and dermoid cysts grow through cisterns, the neural structures may be differentially involved.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that incomplete excision of basal germinal cells of the tumor induce the tumor recurrence [3]. Because the tumor content includes fat and cholesterol, they may also produce an inflammatory reaction leading to meningitis [2, 4, 12, 15]. In our case, complete resection of the tumor’s capsule with emptying of the cyst material was achieved, although the tumor’s capsule ruptured during the procedure.…”
Section: Discussionmentioning
confidence: 70%
“…MRI is useful for the diagnosis of spinal ECs, demonstrating that the tumor is hypo-intense on the T1-weighted view and hyper-intense on the T2-weighted view. However, it is sometimes difficult to detect small cysts, because spinal ECs show the same signal as the cerebrospinal fluid on MRI [12, 13]. Myelography can also be performed to evaluate the deviation of the spinal cord, intradural filling defect, or the blocked subarachnoid space.…”
Section: Discussionmentioning
confidence: 99%
“…X-rays often show a normal image and CT can only display the location and outline of the tumor. On MRI, the tumor is usually isointense or hypointense in T1-weighted images and hyperintense in T2-weighted images and the cyst content has the same signal as the cerebrospinal fluid [17-19]. But these signal characteristics are not always constant and some variations have been reported in the literature [18,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…So subtotal excision tends to be the more common surgical pattern for avoiding possible neural damage [10,18,19,22,23,30]. Subtotal excision also causes great distress for patients and doctors because debris from the tumor may cause an early relapse of symptoms and the spread of cyst contents can cause foreign body reactions and severe complications [2,17,19,23,28,29]. …”
Section: Discussionmentioning
confidence: 99%